Analysis of Mortar Properties with Different Graphite Contents by Partial Replacement of Portland Cement (Research, Society and Development, 2022)
It is known that mortar is a homogeneous mixture of fine aggregates with inorganic binders and water, and may contain additives with properties that improve adhesion or accelerate the hardening of the material. Aiming to improve improvements in the mechanical properties of this composite, this work aimed to analyze its properties through the partial replacement of 5% (T1), 10% (T2) and 15% (T3) of Portland cement by graphite. To evaluate the characteristics, normative tests of compressive strength, tensile strength in diametral compression, adhesion and water absorption by capillarity were carried out. It was possible to verify that as the graphite content increases, there is a reduction in compressive strength, but there is a considerable increase in resistance to traction efforts (traction in diametral compression and adhesion). In this way, it is believed to be possible to use graphite as a partial replacement of Portland cement, which would promote a reduction in environmental pollution, due to the fact that it reduces the amount of cement, consequently reducing the CO2 emission of the mortar.